2019
DOI: 10.1038/s41586-019-1127-1
|View full text |Cite
|
Sign up to set email alerts
|

The emergent landscape of the mouse gut endoderm at single-cell resolution

Abstract: Summary To delineate the ontogeny of the mammalian endoderm, we generated 112,217 single-cell transcriptomes representing all endoderm populations within the mouse embryo until midgestation. By employing graph-based approaches, we modelled differentiating cells for spatio-temporal characterization of developmental trajectories and defined the transcriptional architecture that accompanies the emergence of the first (primitive or extra-embryonic) endodermal population and its sister pluripotent (embryonic) epibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
529
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(556 citation statements)
references
References 56 publications
27
529
0
Order By: Relevance
“…and Clic6, are most prominently expressed in the primitive endoderm and later in other endoderm derivatives (Nowotschin et al, 2019), and in fact LRP2 had been previously identified as a marker of primitive endoderm precursors of the blastocyst (Gerbe et al, 2008). This fits well with the known role of Nanog in the epiblast/primitive endoderm decision occurring in the preimplantation embryo (Bassalert et al, 2018;Frankenberg et al, 2011) and suggests that Lrp2 and Clic6 could be directly repressed by NANOG in epiblast cells of the blastocyst.…”
Section: Discussionsupporting
confidence: 75%
“…and Clic6, are most prominently expressed in the primitive endoderm and later in other endoderm derivatives (Nowotschin et al, 2019), and in fact LRP2 had been previously identified as a marker of primitive endoderm precursors of the blastocyst (Gerbe et al, 2008). This fits well with the known role of Nanog in the epiblast/primitive endoderm decision occurring in the preimplantation embryo (Bassalert et al, 2018;Frankenberg et al, 2011) and suggests that Lrp2 and Clic6 could be directly repressed by NANOG in epiblast cells of the blastocyst.…”
Section: Discussionsupporting
confidence: 75%
“…This identified all the previously known DE lineages ( Fig. 1e) 1,2,9,11 and revealed a surprising number of distinct SM cell types, indicating previously unappreciated mesenchymal diversity in the early foregut ( Fig. 1f; Supplementary Fig.…”
mentioning
confidence: 59%
“…Single cell transcriptomics allows examination of organogenesis at an unprecedented resolution [3][4][5][6] , however, to date studies have either taken a broad overview of many organ systems or focused only on the epithelial component of the developing gut [7][8][9] . To comprehensively characterize the signaling networks orchestrating foregut organogenesis, we performed single cell RNA sequencing (scRNA-seq) of the mouse embryonic foregut at three time points that span early patterning through organ lineage induction: Embryonic day (E) E8.5 (5-10 somites, 's'), E9.0 (12-15s) and E9.5 (25-30s) (Fig.…”
mentioning
confidence: 99%
“…A second cell fate decision starting around E3.5 within the ICM gives rise to the pluripotent epiblast (EPI) and the primitive endoderm (PE), precursors of all embryonic germ layers and extraembryonic yolk sac, respectively 4 . For the most part EPI, PE and TE cells maintain blastocyst-defined lineage assignments throughout subsequent development, with a notable exception for the PE, which was shown to also contribute to otherwise EPI-derived definitive endodermal lineages during post-implantation stages 5,6 .…”
Section: Introductionmentioning
confidence: 99%